ANALISIS KEBIJAKAN HUKUM TERHADAP PENGATURAN TRANSPLANTASI ORGAN DI INDONESIA - Ravfa Sefviar Maharani (CV. Denasya Smart Publisher, 2024)
This study analyzes the legal policies regarding organ transplantation regulations in Indonesia, focusing on the existing legal framework, its strengths and weaknesses, and comparisons with countries that have more advanced organ transplantation practices. The research method used is normative juridical with a statutory and comparative approach. The results show that Indonesia has established a legal foundation for organ transplantation, primarily through Law No. 36 of 2009 on Health, Government Regulation No. 53 of 2021, and Minister of Health Regulation No. 38 of 2016. However, there are still several weaknesses such as unclear rules, lack of donors, and insufficient legal protection for unpaid donors. Compared to countries like Belgium and the United States, Indonesia still lags in terms of system efficiency and organ availability. This study recommends improving legal policies through clarification of ambiguous definitions and provisions, creation of specific regulations, development of better registration and examination systems, and increased public education. Additionally, strengthening medical infrastructure, more stringent law enforcement, and consideration of cultural and religious aspects in policy development are necessary. The implementation of these recommendations is expected to improve the effectiveness and legal protection in organ transplantation practices in Indonesia.